Educational Leadership and Strategy for Facing Generation Z and Alpha in the 5.0 Era at MTs Al-Wardah Tembung - Evy Juliani Siregar; Makmur Syukri (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This study aims to identify and analyze how the importance of inclusive education towards innovative in facing the substance and alpha generations in the 5.0 era. the research method used is a qualitative method with a descriptive approach. The results showed that MTS Al Wardah tembung provided an in-depth understanding of the principal's view of effective strategies in z and alpha generation education. Educational leaders need to consider the needs of generation z and alpha in developing holistic strategies for a bright future in the 5.0 era. Educational leaders also need to understand the unique needs of these generations such as collaborative learning the use of technology, and active engagement in the educational process. Responsive and innovative strategies and creating inspiring and inclusive learning environments are key in supporting the electric growth of generation z and Alpha.